What are Migration Networks? - Thomas K. Bauer; Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2000)
Migration networks are usually captured by the number of people from the migrant?s country in the host region. Using Mexican migration data, we analyze the effects of the usual network variable and two additional origin-village-specific variables on migrants? location choice.
Keywords: F22; J61; 330; Location choice; networks; immigration; Migranten; Ethnische Gruppe; Soziales Netzwerk; Wohnstandort; Mexikaner; Schätzung; USA